A proppant with anti-scaling and corrosion-inhibiting properties and preparation method thereof

By mixing the scale inhibitor and silica with the resin and dispersing it in a two-phase solvent of oil and water, a proppant with anti-scattering corrosion inhibition property is prepared, which solves the problem of salt scale formation due to water oversaturation and incompatibility of the proppant laying layer, which improves the flow diversion ability and permeability, and extends the anti-scattering effect.

CN116410732BActive Publication Date: 2025-02-28PETROCHINA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111678889.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-02-28
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

During the hydraulic fracturing transformation of oil and gas wells, the proppant laying layer is prone to form salt scale due to the supersaturation and incompatibility of high mineralization water or external clean water, resulting in a decrease in the diversion capacity and affecting normal production.

Method used

By adding the scale inhibitor and silica to the resin and mixing them evenly, then adding oil and water to a mixed solvent of two phases of oil and water to disperse them into liquid droplets, and finally adding a curing agent to cure the droplets and drying at low temperatures, a proppant with anti-scale corrosion resistance is prepared.

Benefits of technology

The proppant can be reused under specific working conditions. The scale inhibitor is dissolved in the output water and gradually releases the scale inhibitor, which improves the flow diversion ability and permeability, extends the scale anti-scaling effect, and has high compressive strength and strong anti-brokening ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003453353180000121
    Figure BDA0003453353180000121
  • Figure BDA0003453353180000122
    Figure BDA0003453353180000122
  • Figure BDA0003453353180000131
    Figure BDA0003453353180000131
Patent Text Reader

Abstract

The present invention discloses an anti-scaling proppant capable of repeatedly adsorbing, retaining, desorbing and releasing a scale inhibitor and a preparation method thereof. The method comprises the following steps: uniformly mixing an organic phosphonate and nano-scale silica powder and interposing the mixture into a resin, dispersing the mixture into small droplets in an oil-water two-phase solvent, then adding a curing agent to solidify the droplets, and drying the mixture at a low temperature to prepare a proppant having a certain strength. When the proppant of the present invention is used under specific working conditions, the scale inhibitor in the proppant particles dissolves in the produced water, and the scale inhibitor is gradually released. The scale inhibitor in the proppant prepared by the present invention is distributed to the interior and surface of the proppant by means of encapsulation, adsorption, etc., so that a high load of effective components of the scale inhibitor can be achieved. The scale inhibitor can be accompanied by fracturing construction, mixed with the fracturing proppant and laid in the fracturing crack, and the scale inhibitor in the scale inhibitor particles gradually dissolves in the formation water or the fracturing fluid, so as to achieve the purpose of inhibiting the scaling of the produced fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum extraction and relates to a proppant with anti-scaling and corrosion-inhibiting performance and a preparation method thereof. Background Art

[0002] During the hydraulic fracturing process of oil and gas wells, a large amount of fracturing fluid is injected into the deep formation, and a certain proportion of hard granular inorganic materials are added as proppants for artificial fractures. Common materials include natural quartz sand or artificially fired ceramsite. In this way, after the fracturing construction is completed, a proppant layer of a certain width and height is formed in the formation. The proppant layer with high conductivity ensures that the oil and gas flow in the deep formation can smoothly enter the wellbore along the fracture channel and be finally produced. However, the highly mineralized water in the formation fluid, or the external clean water introduced into the fracturing fluid and other media will form salt scales of varying degrees in the proppant layer due to oversaturation or water incompatibility, causing the proppant's conductivity to decrease and affecting normal production.

[0003] To solve the scaling problem of fracturing formations, the common method at home and abroad is to regularly squeeze acid or liquid chemicals such as scale removers and scale inhibitors into the formation from the wellhead after the oil and gas wells are put into production. There are also methods of adding liquid scale inhibitors to the fracturing fluid, but liquid scale inhibitors may be incompatible with certain gel systems because they interact with metal cross-linking agents; there is also a practice of adding a certain proportion of scale inhibitor particles to the proppant.

[0004] For anti-scaling proppant particles, the processes that have been commercially applied include: 1. Inorganic proppant particles impregnated with anti-scaling agents mixed with fracturing proppant; such as anti-scaling agent impregnated proppant (SIIP). 2. Special high-strength anti-scaling particles mixed with fracturing proppant; Jonathan et al. SPE 107707 reported that liquid anti-scaling agents with high content of active components were mixed with high-strength substrates to ensure the complete adsorption of anti-scaling agents on the surface of solid substrates, and achieved good application results on site. 3. Fracturing anti-scaling gel microspheres. Mukhopadhyay et al. proposed the process of fracturing anti-scaling gel microspheres in the paper SPE 173584, which mainly utilizes the porous and viscoelastic characteristics of biodegradable polymer hydrogels, and achieves a certain strength and compressive resistance through chemical modification and cross-linking. Then the slightly soluble anti-scaling microspheres are embedded in the gel to make anti-scaling gel balls of specific sizes. Chinese patent number: CN105602539B discloses a scale inhibitor formula and preparation method for multi-fracture fracturing in oil fields, which is used for fracturing with scale-inhibiting particles composed of a coating agent, a scale inhibitor and an adhesive. Chinese patent number: CN105038750B discloses a slow-release scale inhibitor in oil well fractures and its preparation method, which is composed of organic phosphonate, sodium gluconate, sodium ascorbate, and sodium ethylenediamine di-o-phenylacetate; the skeleton is composed of rosin-modified phenolic resin, bisphenol A phenolic epoxy resin, polyethylene glycol and hexamethylenetetramine. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a proppant with anti-scaling and corrosion inhibition performance and a preparation method thereof, which effectively improves the conductivity and permeability of the proppant.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a proppant with anti-scaling and corrosion-inhibiting properties, comprising:

[0008] The scale inhibitor and silica are added to the resin and mixed evenly, and then added to an oil-water two-phase mixed solvent to disperse into droplets, and then a curing agent is added to solidify the droplets, and then low-temperature drying is performed to obtain a proppant with scale and corrosion inhibition properties.

[0009] Preferably, the mass ratio of the resin to the scale inhibitor is 1:1-3:1, the mass ratio of the scale inhibitor to silicon dioxide is 3:1-4.5:1; and the molar ratio of the resin to the curing agent is 1:0.03-1:0.3.

[0010] Preferably, the curing agent is at least one of an imidazole curing agent, a polyamide curing agent, an aromatic curing agent and an alicyclic curing agent.

[0011] Preferably, the imidazole curing agent adopts one of benzyl imidazole, cyanoethyl imidazole, ethyl imidazole and benzyl imidazole, the polyamide curing agent adopts one of polyamide curing agent 115, polyamide curing agent H3260 and polyamide curing agent 5140, the aromatic curing agent adopts diaminodiphenyl sulfone or 4-chloro-o-phenylenediamine; the alicyclic curing agent adopts diaminodicyclohexylmethane.

[0012] Preferably, the resin is one of bisphenol A epoxy resin, polyester resin and furan resin, and the scale inhibitor is at least one of organic phosphonate, organic phosphonate and maleic anhydride copolymer.

[0013] Preferably, the organic phosphonate is at least one of polyoxyethylene fatty ether phosphate, phosphinyl polyacrylate, polyoxyethylene pyrophosphate and aminomethylene phosphate; the organic phosphate is at least one of hydroxyethylene diphosphonate, 2-phospho-1,2,4-tricarboxylic acid butane, ethylenediaminetetramethylenephosphonate and hexamethylenediaminetetramethylenephosphonate; the maleic anhydride copolymer is at least one of olefin aminomethylphosphonic acid-acrylic acid-maleic anhydride terpolymer, phosphine-containing hydrolyzed polymaleic anhydride polymer, MA-AA-AMPS terpolymer and MA-SAS-AA water-soluble polymer antiscalant.

[0014] Preferably, the oil-water two-phase mixed solvent adopts at least one of a water-soluble solvent and an oil-soluble solvent; the mass fraction of the water-soluble solvent in the mixed solvent is 0.5wt% to 8wt%; the mass fraction of the oil-soluble solvent in the mixed solvent is 0.1wt% to 5wt%.

[0015] Preferably, the oil-soluble solvent is at least one of sorbitan trioleate, sorbitan stearate, diethylene glycol monostearate and polyoxyethylene oleyl alcohol ether; and the water-soluble solvent is at least one of methanol, ethanol, ethylene diether, acetone, dichloromethane and chloroform.

[0016] Preferably, the specific conditions of low-temperature drying are: drying temperature 55° C.-85° C., and drying time 2 h-6 h.

[0017] A method for preparing a proppant with anti-scaling and corrosion-inhibiting properties is prepared by the above-mentioned preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial technical effects:

[0019] A proppant with anti-scaling and corrosion-inhibiting properties is reusable. When used under specific working conditions, the scale inhibitor in the proppant particles dissolves in the produced water and gradually releases the scale inhibitor. The proppant with anti-scaling and corrosion-inhibiting properties of the present invention is added with a composite material of an organic scale inhibitor, a resin, etc., so that the proppant has a certain strength of anti-crushing and anti-scaling properties, and will not cause the conductivity and permeability to decrease due to the scaling of the proppant filling layer. In addition, the scale inhibitor in the proppant prepared by the present invention is distributed to the inside and surface of the proppant by means of wrapping, adsorption, etc., so that a high load of the effective components of the scale inhibitor can be achieved; the proppant of the present invention has high compressive strength and strong anti-crushing ability, and can be mixed with commonly used proppant in different proportions and injected into the wellbore and formation without changing the pumping process and injection equipment; the scale inhibitor can accompany the fracturing construction, and be mixed with the fracturing proppant and laid in the fracturing crack, and the scale inhibitor in the scale inhibitor particles gradually dissolves in the formation water or fracturing fluid, so as to achieve the purpose of inhibiting the scaling of the produced fluid.

[0020] The proppant prepared by the present invention has a very high specific surface area. After the initially loaded scale inhibitor is dissolved and released, it can be reused, mainly by squeezing a high concentration of scale inhibitor into the fracturing cracks. The scale inhibitor is adsorbed and retained in the pores of the proppant, and then gradually released after being soaked in the production fluid. Compared with the scale inhibitor effect of conventional squeezing scale inhibitors, the scale inhibitor effect of the present invention has a longer effective period. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of a proppant prepared in the present invention;

[0022] Figure 2Schematic diagram of the anti-scaling agent prepared in the example; DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0024] Embodiment 1:

[0025] The first step is to evenly disperse 30g of ethylenediaminetetramethylene sodium phosphate and 8g of nano-silicon dioxide powder into 50g of bisphenol A epoxy resin; the second step is to add 2wt% of sorbitan trioleate (Span85) and 1wt% of methanol to the above resin under magnetic stirring, dilute it 8-10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 15-20min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 1wt% of dehydrated sorbitan stearic acid, and stir it with a mechanical stirrer at 1500r for 10min to obtain a mixture B; the fourth step is to dissolve the mixture B in 25ml of dichloromethane, and stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 1.8-2g of benzyl imidazole to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in the mixture C are evenly mixed, heat the fluid to 60°C, stand for 2h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm, heat the mixed solution to 65°C, dry for 4h, and wait until the volatile solvent evaporates completely to obtain the anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and dry them with hot air for 4h to obtain the final anti-scaling proppant particles.

[0026] The solid anti-scaling proppant particles obtained according to the above scheme have a corresponding density of 1.1 g / cm 3 , particle size is 0.5mm, and scale inhibitor loading rate is 25%-30%.

[0027] Embodiment 2:

[0028] The first step is to uniformly disperse 35g of polyoxyethylene fatty ether phosphate and 9g of nano-silicon dioxide powder into 45g of bisphenol A epoxy resin; the second step is to add 3wt% of diethylene glycol monostearate and 1wt% of ethanol to the above resin under magnetic stirring, dilute it 8 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 20min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 1wt% of polyoxyethylene oleyl alcohol ether, and stir it with a mechanical stirrer at 1500r for 15min to obtain a mixture B; the fourth step is to dissolve the mixture B in 30ml of chloroform, stir it at 2000r for 25-30min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-8μm. The fifth step is to add 15g of curing agent H3260 to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid temperature to 60°C, and stand at a constant temperature for 1-2h until the resin is cured to form solid small particles with a particle size of 100nm-10μm, heat the mixed solution to 60-80°C, dry for 3-4h, and wait until the volatile solvent evaporates completely to obtain the anti-scaling proppant suspension D. The sixth step is to filter the anti-scaling proppant suspension D, and dry the filtered solid components with hot air for 4h to obtain the final anti-scaling proppant particles.

[0029] The solid anti-scaling proppant particles obtained according to the above scheme have a corresponding density of 1.2 g / cm 3 , particle size is 0.3mm, and scale inhibitor loading rate is 33%-35%.

[0030] Embodiment 3:

[0031] The first step is to uniformly disperse 40 wt% of hydroxyethylene diphosphonate and 10 g of nano-silicon dioxide powder into 40 g of bisphenol A epoxy resin; the second step is to add 3.5 wt% of polyoxyethylene fatty ether phosphate and 2 wt% of methanol-ethanol mixture to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 2000 r for 20 min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 1.5 wt% of diethylene glycol monostearate, and stir it with a mechanical stirrer at 2000 r for 15 min to obtain a mixture B; the fourth step is to dissolve the mixture B in 30 ml of ethylene diether, stir it at 2000 r for 25-30 min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100 nm-5 μm. The fifth step is to add 1.6g of curing agent ethylene diether to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid temperature to 60°C, and stand at a constant temperature for 2h until the resin is cured to form solid small particles with a particle size of 100nm-5μm, heat the mixed solution to 80°C, dry for 4h, and wait until the volatile solvent evaporates completely to obtain the anti-scaling proppant suspension D. The sixth step is to filter the anti-scaling proppant suspension D, and dry the filtered solid components with hot air for 4h to obtain the final anti-scaling proppant particles.

[0032] The solid anti-scaling proppant particles obtained according to the above scheme have a corresponding density of 1.2 g / cm 3 , particle size is 0.4mm, and scale inhibitor loading rate is 35%-40%.

[0033] Embodiment 4:

[0034] The first step is to uniformly disperse 30g of ethylenediaminetetramethylenephosphonate and 10g of nano-silica powder into 60g of polyester resin; the second step is to add 2wt% of diethylene glycol monostearate and 3wt% of ethanol to the above resin under magnetic stirring, dilute it 8 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 20min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 2wt% of dehydrated sorbitan stearic acid, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in 25ml of chloroform, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 2.0g of benzyl imidazole to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 70°C, stand for 2h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 60°C and dried for 6h until the volatile solvent evaporates completely to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and then dry them with hot air for 6h to obtain the final anti-scaling proppant particles.

[0035] The solid anti-scaling proppant particles obtained according to the above scheme have a corresponding density of 1.1 g / cm 3 , particle size is 0.54mm, antiscalant loading rate is 24.5%-26.5%.

[0036] Embodiment 5:

[0037] The first step is to uniformly disperse 25g of polyoxyethylene fatty ether phosphate and 6g of nano-scale silicon dioxide powder into 75g of furan resin; the second step is to add 2wt% of polyoxyethylene oleyl alcohol ether and 0.2wt% of ethylene glycol to the above resin under magnetic stirring, dilute it 9 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 20min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 0.5wt% of dehydrated sorbitan stearic acid, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in 25ml of acetone, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 1.8 benzyl imidazole to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 1.5h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 68°C and dried for 5h, and the volatile solvent is completely evaporated to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and dry them with hot air for 5h to obtain the final anti-scaling proppant particles.

[0038] The solid anti-scaling proppant particles obtained according to the above scheme have a corresponding density of 1.2 g / cm 3 , particle size is 0.55mm, and scale inhibitor loading rate is 26-32%.

[0039] Embodiment 6:

[0040] The first step is to uniformly disperse 42g of phosphinyl polyacrylate and 16g of nano-silica powder into 70g of furan resin; the second step is to add 5wt% of polyoxyethylene oleyl alcohol ether and 1.5wt% of ethylene glycol to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 20min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 3wt% of dehydrated sorbitan stearic acid, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in 30ml of acetone, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 2.2g of ethylimidazole to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 1.5h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 55°C and dried for 6h, and the volatile solvent is completely evaporated to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and then dry them with hot air for 5h to obtain the final anti-scaling proppant particles.

[0041] Embodiment 7:

[0042] The first step is to uniformly disperse 35g of hexamethylenediaminetetramethylenephosphonate and 12g of nano-silica powder into 75g of furan resin; the second step is to add 8wt% of polyoxyethylene oleyl alcohol ether and 3wt% of ethylene glycol to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 15min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 5wt% of sorbitan trioleate, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in a 30m methanol and ethanol mixture, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 2.2g of polyamide curing agent 115 to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 1.5h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 85°C and dried for 6h, and the volatile solvent is completely evaporated to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and dry them with hot air for 5h to obtain the final anti-scaling proppant particles.

[0043] Embodiment 8:

[0044] The first step is to uniformly disperse 35g of olefin aminomethylphosphonic acid-acrylic acid-maleic anhydride terpolymer and 12g of nano-silica powder into 75g of polyester resin; the second step is to add 5wt% of polyoxyethylene oleyl ether and 2wt% of ethylene glycol to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 15min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 0.5wt% of sorbitan trioleate, and stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B; the fourth step is to dissolve the mixture B in 30ml of a mixture of methanol and ethanol, and stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 2.4g of polyamide curing agent H3260 to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 2h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 70°C and dried for 6h, and the volatile solvent is completely evaporated to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and dry them with hot air for 4h to obtain the final anti-scaling proppant particles.

[0045] Embodiment 9:

[0046] The first step is to uniformly disperse 35g of a mixture of phosphine-containing hydrolyzed polymaleic anhydride polymer and aminomethylene phosphate and 8g of nano-scale silicon dioxide powder into 35g of polyester resin; the second step is to add 3wt% polyoxyethylene oleyl alcohol ether and 0.3wt% ethylene glycol ether to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 15min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 0.1wt% sorbitan trioleate, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in 25ml of a mixture of ethylene glycol and acetone, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 2.4g of polyamide curing agent 5140 to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 2h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 70°C and dried for 6h, and the volatile solvent is completely evaporated to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and then dry them with hot air for 4h to obtain the final anti-scaling proppant particles.

[0047] Embodiment 9:

[0048] The first step is to uniformly disperse 40g of a mixture of ethylenediaminetetramethylene phosphate and MA-AA-AMPS terpolymer and 9g of nano-scale silicon dioxide powder into 35g of polyester resin; the second step is to add 3wt% of polyoxyethylene oleyl alcohol ether and 0.3wt% of acetone to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 15min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 0.1wt% of sorbitan trioleate, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in 25ml of a mixed solution of dichloromethane and acetone, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 2.1g of diaminodicyclohexylmethane to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 2h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 70°C and dried for 6h, and the volatile solvent is completely evaporated to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and then dry them with hot air for 4h to obtain the final anti-scaling proppant particles.

[0049] Embodiment 10:

[0050] The first step is to uniformly disperse 40g of a mixture of ethylenediaminetetramethylene phosphate and a water-soluble polymer of MA-SAS-AA and 9g of nano-silicon dioxide powder into 35g of a polyester resin; the second step is to add 5wt% of polyoxyethylene oleyl alcohol ether and 2wt% of acetone to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 15min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 0.2wt% of sorbitan trioleate, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in 25ml of a mixed solution of dichloromethane and acetone, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 2.1g of diaminodiphenyl sulfone to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 2h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 70°C and dried for 6h until the volatile solvent evaporates completely to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and then dry them with hot air for 4h to obtain the final anti-scaling proppant particles.

[0051] Embodiment 11:

[0052] The first step is to uniformly disperse 38g of a mixture of oxyethylene fatty ether phosphate and phosphinyl polyacrylate and 9g of nano-scale silicon dioxide powder into 35g of furan resin; the second step is to add 5wt% of polyoxyethylene oleyl alcohol ether and 2wt% of methanol to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 15min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 0.2wt% of sorbitan trioleate, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in 25ml of a mixed solution of dichloromethane and acetone, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 2.1g of benzyl imidazole to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 2h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 85°C and dried for 6h until the volatile solvent evaporates completely to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and dry them with hot air for 4h to obtain the final anti-scaling proppant particles.

[0053] Embodiment 12:

[0054] The first step is to uniformly disperse 38g of a mixture of oxyethylene fatty ether phosphate and phosphinyl polyacrylate and 9g of nano-scale silicon dioxide powder into 35g of furan resin; the second step is to add 5wt% of polyoxyethylene oleyl alcohol ether and 3wt% of methanol to the above resin under magnetic stirring, dilute it 10 times with deionized water, and then stir it with a mechanical stirrer at 1500r for 15min to obtain a resin aqueous dispersion A; the third step is to mix the resin aqueous dispersion A with 0.8wt% of sorbitan trioleate, stir it with a mechanical stirrer at 1500r for 10 to obtain a mixture B, and the fourth step is to dissolve the mixture B in 25ml of a mixed solution of dichloromethane and acetone, stir it at 2000r for 25min to form a mixture C in which the aqueous phase exists in the form of small droplets of 100nm-10μm. The fifth step is to add 1.9g of 4-chloro-o-phenylenediamine to the mixture C and stir at a high speed of 3000r for 30min until the curing agent and the volatile solvent in C are evenly mixed, heat the fluid to 65°C, stand for 2h, and solidify the resin to form small solid particles with a particle size of 100nm-10μm. The mixed solution is heated to 85°C and dried for 6h, and the volatile solvent is completely evaporated to obtain an anti-scaling proppant suspension D. The sixth step is to centrifuge the anti-scaling proppant suspension D, filter the solid components, and then dry them with hot air for 4h to obtain the final anti-scaling proppant particles.

[0055] Experimental test analysis: The following analysis was performed using Example 1 as the test sample

[0056] Conductivity test

[0057] (1) Experimental standard: refer to SY / T6302-2009 “Recommended method for evaluating short-term conductivity of fracturing proppant packing layer”.

[0058] (2) Experimental purpose: At a formation temperature of 80°C and pressures of 30 MPa and 40 MPa, standard brine was used as the experimental liquid to test the conductivity of the proppant alone and after adding 2% solid anti-scaling agent to the proppant under laminar flow conditions. Based on the experimental results, the influence of 2% solid anti-scaling agent on the conductivity of the proppant was determined.

[0059] (3) Experimental equipment:

[0060] Equipment name: FCS-842 proppant conductivity evaluation system from Core Lab, USA

[0061] Technical indicators: Closing pressure 0-140MPa; heating temperature 20-177℃; injection flow rate 0.0001-50ml / min.

[0062] (4) Experimental procedures:

[0063] According to the instrument operating procedures, apply closing pressure to the sample for a sufficient period of time to allow the proppant filling layer to reach a semi-stable state, and allow the liquid to flow through the filling layer under a certain closing pressure. When the liquid flows through the proppant filling layer under different closing pressure conditions, the proppant filling seam width, pressure difference and flow rate should be measured. Calculate the conductivity and permeability of the proppant filling layer. Under the required flow rate and room temperature conditions, there should be no non-Darcy flow or inertial effects. After the experiment is completed under one closing pressure, the closing pressure value can be increased to another value, and a certain amount of time is allowed to allow the proppant filling layer to reach a semi-stable state. Conduct the experiment again to obtain the required data, determine the conductivity of the proppant filling layer under this condition, and repeat this procedure until all experiments with the designed closing pressure are completed.

[0064] (5) Calculation of permeability and conductivity of filling layer and liquid under laminar flow conditions

[0065]

[0066] Where k is the permeability of the mixture filling layer, μm 2 kW f is the conductivity of the mixture filling layer, μm 2 ·cm; μ is the viscosity of the experimental liquid under the experimental temperature conditions, mPa·s; Q is the flow rate in the crack, cm 3 / s; L is the length of the pressure measuring section, cm; W is the width of the filling layer, cm; W f is the filling layer thickness, cm; Δp is the pressure difference at both ends of the test section, kPa.

[0067] Table 1 Test results of flow conductivity

[0068]

[0069] Laboratory crush test:

[0070] (1) Experimental standard: refer to SY / T5108-2014 “Proppant Performance Test Method for Hydraulic Fracturing and Gravel Packing Operations”.

[0071] (2) Experimental purpose: Under the conditions of formation temperature of 80°C and formation effective closure pressure of 30,40MPa, the crushing rate of the mixture after adding 2% solid anti-scaling agent to the proppant was tested. Based on the experimental results, the crushing rate of the mixture after 2% solid anti-scaling agent was mixed with the proppant was determined.

[0072] (3) Experimental equipment:

[0073] Equipment name: Domestic proppant crushing rate measuring device, of which the ultra-high pressure plunger pump is an American product and the 3D printer is a German product. Technical indicators: Maximum closing pressure 140MPa; pressure sensor accuracy 0.04%; crack width control 0.1-15mm.

[0074] (4) Experimental procedures:

[0075] ① Weigh the sample mass m s , pour it into the crushing chamber steadily, and the paving surface should be as flat as possible;

[0076] ②Insert the piston into the crushing chamber containing the weighed sample. No external force shall be applied except gravity. Rotate the piston 180° / time in a clockwise direction. No pressure shall be applied to ensure that the proppant sample laying surface is flush.

[0077] ③ Carefully lift the crushing chamber and place it directly into the press, so that it is directly under the press straightening plate; do not shake or bump the crushing chamber, as this may cause the proppant filling to sink, resulting in changes in the particle filling shape or particle rearrangement when pressurized.

[0078] ④ According to the actual application on site, calculate the required stress F tc according to the following formula:

[0079]

[0080] Where, Ftc is the force in the crushing chamber, N; σ is the stress on the sample, MPa; dcell is the inner diameter of the crushing chamber, mm.

[0081] ⑤ Add the set pressure to the crushing chamber within 1 minute and maintain the pressure for 2 minutes. The time to reach the rated pressure should be limited to within 5% of the loading rate time. If it exceeds ±2.5% of the set pressure, the test should be stopped and restarted with a new sample.

[0082] ⑥ After unloading the pressure, remove the crushing chamber from the press. Carefully pour the sample into the group sieve, scrape out the sample at the bottom of the crushing chamber, and ensure that all the sample is poured out.

[0083] ⑦Put the group sieve into the vibrating sieve machine and vibrate for 10 minutes, and carefully weigh the mass m of the crushed material in the pan. pan And make records with an accuracy of 0.lg.

[0084] (5) Calculation of crushing rate:

[0085]

[0086] In the formula, m pan’ is the sample breakage rate, expressed as a percentage; m pan is the mass of particles produced in the experiment, g; m s is the mass of the sample, g.

[0087] Experimental results:

[0088] Table 2 Crushing test results

[0089]

[0090]

Claims

1. A method for preparing a proppant with anti-scaling and corrosion inhibition properties, characterized in that: include, After adding the scale inhibitor and silica to the resin and mixing them evenly, 2wt% of an oil-soluble solvent and 1wt% of a water-soluble solvent are added to the resin for dispersion, and then diluted with deionized water by 8-10 times to obtain a resin aqueous dispersion A; then the resin aqueous dispersion A is mixed with 1wt% of an oil-soluble solvent to obtain a mixture B; then the mixture B is dissolved in 25ml of a water-soluble solvent to obtain droplets, a curing agent is added to solidify the droplets, and low-temperature drying is performed to obtain a proppant with anti-scaling and corrosion inhibition properties; The mass ratio of the resin to the scale inhibitor is 1:1-3:1, the mass ratio of the scale inhibitor to silicon dioxide is 3:1-4.5:1; the molar ratio of the resin to the curing agent is 1:0.03-1:0.3; The oil-soluble solvent is at least one of sorbitan trioleate, sorbitan stearate, diethylene glycol monostearate and polyoxyethylene oleyl alcohol ether; the water-soluble solvent is at least one of methanol, ethanol, ethylene diether, acetone, dichloromethane and chloroform.

2. The method for preparing a proppant with anti-scaling and corrosion inhibition properties according to claim 1, characterized in that: The curing agent is at least one of an imidazole curing agent, a polyamide curing agent, an aromatic curing agent and an alicyclic curing agent.

3. The method for preparing a proppant with anti-scaling and corrosion inhibition properties according to claim 2, characterized in that: The imidazole curing agent adopts one of benzyl imidazole, cyanoethyl imidazole, ethyl imidazole and benzyl imidazole, the polyamide curing agent adopts one of polyamide curing agent 115, polyamide curing agent H3260 and polyamide curing agent 5140, the aromatic curing agent adopts diaminodiphenyl sulfone or 4-chloro-o-phenylenediamine; the alicyclic curing agent adopts diaminodicyclohexylmethane.

4. The method for preparing a proppant with anti-scaling and corrosion inhibition properties according to claim 1, characterized in that: The resin is one of bisphenol A epoxy resin, polyester resin and furan resin, and the scale inhibitor is at least one of organic phosphonate, organic phosphonate and maleic anhydride copolymer.

5. The method for preparing a proppant with anti-scaling and corrosion inhibition properties according to claim 4, characterized in that: The organic phosphonate is at least one of polyoxyethylene fatty ether phosphate, polyoxyethylene pyrophosphate and aminomethylene phosphate; the organic phosphate is at least one of hydroxyethylene diphosphonate, ethylenediamine tetramethylene phosphonate and hexamethylene diamine tetramethylene phosphonate; the maleic anhydride copolymer is at least one of olefin aminomethylphosphonic acid-acrylic acid-maleic anhydride terpolymer, phosphine-containing hydrolyzed polymaleic anhydride polymer, MA-AA-AMPS terpolymer and MA-SAS-AA water-soluble polymer antiscalant.

6. The method for preparing a proppant with anti-scaling and corrosion inhibition properties according to claim 1, characterized in that: The specific conditions of the low-temperature drying are: drying temperature 55° C.-85° C., and drying time 2 h-6 h.

7. A proppant with anti-scaling and corrosion inhibition properties, characterized in that: Prepared based on the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Slow-release anti-scaling agent in oil well fracture and preparation method thereof

    CN105038750B

  • Formula and preparation method of scale inhibitor for multi-fracture fracturing in oil field

    CN105602539B

  • Water-controlling and scale-inhibiting coated proppant and preparation method thereof

    CN111621284A